Ragam Metode Pemodelan Perilaku Evakuasi Kebakaran di dalam Bangunan - Dessy Syarlianti; Himasari Hanan (Archvisual: Jurnal Arsitektur dan Perencanaan, 2021)
Building safety design relates to the ease and effectiveness of evacuation. One of the most influential aspects is human behavior. In building fires, many computational and mathematical simulation models have been developed to understand the phenomenon of behavior that occurs. However, it is rare to discuss a comprehensive review of the development of the modeling method and its potential application in Indonesia. The purpose of this study is to examine several methods of modeling fire evacuation behavior in buildings to find potential and obstacles to their application, especially in the Indonesian context through literature review. In Indonesia, architectural research related to fire evacuation behavior is scarce; most focus on compliance with prescriptive rules, extinguishers placement, and installation of compartments and passive extinguishing systems. The potential aspect to be included in the evacuation behavior model is the social culture of Indonesia regarding differences in perceiving and gaining environmental information.